Peningkatan Minat dan Motivasi Siswa SMK terhadap Kompetensi Internet of Things (IoT) melalui Pelatihan: Mendorong Inovasi Bisnis dalam Sektor Pariwisata Digital - Jessica Ignatia Tambunan; Syafrudi Syafrudi; Putu Ketri Handayani; Futri Zalzabilah Ray (Yayasan Literasi Sains Indonesia, 2025)
Vocational education, such as Vocational High Schools (SMK), faces challenges such as limited facilities and low digital literacy, particularly in developing technology-based competencies for the digital tourism sector. This study aims to determine the extent to which Internet of Things (IoT) training can increase vocational high school students' interest and motivation in developing competencies related to digital tourism innovation. This study uses a qualitative approach with data collection techniques through semi-structured interviews with vocational high school students directly involved in training activities. Focus Group Discussions (FGDs) were chosen to delve deeper into students' perceptions and experiences regarding their understanding and interest in the application of Internet of Things (IoT) technology in the tourism industry. This research instrument used semi-structured interviews, focus group discussions (FGDs), observation, and documentation. The results show that case study-based training helps students understand the application of IoT in a concrete manner that is relevant to their majors. Students showed increased enthusiasm, curiosity, and analytical skills in linking IoT to business innovation opportunities in the tourism sector. The conclusion of this study is that IoT training can be a strategy in preparing a skilled and adaptive workforce in the digital era.